2011
DOI: 10.1590/s0001-37652011000400027
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective, cardioprotective, and renal-protective effects of organic and conventional grapevine leaf extracts (Vitis labrusca var. Bordo) on Wistar rat tissues

Abstract: The purpose of this study was to evaluate the beneficial effects of organic and conventional grapevine (Vitis labrusca L.) leaf extracts in reducing hydrogen peroxide-induced stress in the liver, heart and kidney of Wistar rats by measuring lipids and proteins damages (carbonyl assay), as well as the activity of the antioxidant enzymes superoxide dismutase and catalase. The preincubation with 5 mg/mL of organic and conventional grapevine (Vitis labrusca L.) leaf extracts prevented both lipids and proteins oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 33 publications
6
34
0
Order By: Relevance
“…grape juices (Dani et al 2007(Dani et al , 2008a and grapevine leaves extracts (Dani et al 2010). With regards to the content of catechin, the conventional extract showed higher values than the organic extract, which corroborates fi ndings in grapevine leaves extracts, both organic and conventional, of V. labrusca (Dani et al 2010, Oliboni et al 2011. Many factors can affect the amount of phenolic compounds, among them, genetic factors, climate, soil conditions, degree of ripeness, postharvest storage and growth method (organic or conventional) (Mikašauskaitė et al 2013).…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…grape juices (Dani et al 2007(Dani et al , 2008a and grapevine leaves extracts (Dani et al 2010). With regards to the content of catechin, the conventional extract showed higher values than the organic extract, which corroborates fi ndings in grapevine leaves extracts, both organic and conventional, of V. labrusca (Dani et al 2010, Oliboni et al 2011. Many factors can affect the amount of phenolic compounds, among them, genetic factors, climate, soil conditions, degree of ripeness, postharvest storage and growth method (organic or conventional) (Mikašauskaitė et al 2013).…”
Section: Resultssupporting
confidence: 62%
“…This result was already observed in grapevine leaves from Vitis labrusca (Dani et al 2010), and in grape juices, where organic juice was shown to be richer in polyphenols than conventional juice (Dani et al 2008a). Grapevines leaves are rich in phenolic compounds and have shown signifi cant antioxidant activity in vitro and in vivo (Monagas et al 2006, Kosar et al 2007, Orhan et al 2007, Pari and Suresh 2008, Dani et al 2010, Oliboni et al 2011.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…It is therefore a very popular tool for analysing data that arise in many scientific disciplines, for instance biology (e.g., Soares et al 2011, Juliá and Peris 2010, Camargo et al 2011, biomedical and medical sciences (e.g., Camacho et al 2010, Oliboni et al 2011, earth sciences (e.g., Fontana et al 2010, Rangel et al 2011, social sciences (e.g., Conte et al 2011), economics (e.g., Misztal 2011), ergonomics (e.g., Bin andRichardson 2010, Zadry et al 2011), and of course agriculture (e.g., Chełkowski et al 2000, Cheng et al 2010, Lakhesar et al 2010, Bandehagh and Hossein Zadeh Moghbeli 2011, Cherati et al 2011, Heidari Zooleh et al 2011, Herrero et al 2011, Kesavacharyulu et al 2011, Rogiers et al 2011.…”
Section: Introductionmentioning
confidence: 99%